Potencjał diagnostyczny śliny w screeningu chorób wirusowych = Diagnostic potential of saliva in the screening of viral diseases - Wędrowska, Ewelina; Simińska, Edyta; Wandtke, Tomasz; Wędrowski, Mateusz; Piskorska, Elżbieta (Journal of Education, Health and Sport, 2016)
Wędrowska Ewelina, Simińska Edyta, Wandtke Tomasz, Wędrowski Mateusz, Piskorska Elżbieta. Potencjał diagnostyczny śliny w screeningu chorób wirusowych = Diagnostic potential of saliva in the screening of viral diseases. Journal of Education, Health and Sport. 2016;6(1):147-156. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45142 http://ojs.ukw.edu.pl/index.php/johs/article/view/45142 https://pbn.nauka.gov.pl/works/704038 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Potencjał diagnostyczny śliny w screeningu chorób wirusowych Diagnostic potential of saliva in the screening of viral diseases Ewelina Wędrowska1, Edyta Simińska2, Tomasz Wandtke1, Mateusz Wędrowski3, Elżbieta Piskorska4 1Zakład Genoterapii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 2Katedra i Zakład Toksykologii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 3Zakład Pozytonowej Tomografii Emisyjnej i Diagnostyki Molekularnej, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 4Katedra Patobiochemii i Chemii Klinicznej, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 1Department of Gene Therapy, Faculty of Medicine, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 2Department of Toxicology, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 3Department of Positron Emission Tomography and Molecular Diagnostics, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 4Department of Pathobiochemistry and Clinical Chemistry, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland Streszczenie Wprowadzenie: W ostatnich latach potwierdzono, że większość substancji znajdujących się w surowicy krwi, obecnych jest również w ślinie. Wykazano także korelację pomiędzy poziomem substancji występujących w ślinie, ze zmianami zachodzącymi w surowicy krwi. Coraz bardziej podkreśla się liczne zalety śliny jako materiału do badań diagnostycznych, w porównaniu z innymi płynami ustrojowymi. W ostatnich dekadach wskaźniki zachorowalności i umieralności z powodu chorób wirusowych uległy znaczącej poprawie. Jednakże zbyt późna wykrywalność zakażeń wirusowych jest nadal poważnym problemem. Cel pracy: Celem pracy jest przedstawienie możliwości wykorzystania śliny w screeningowych badaniach chorób wirusowych. Skrócony opis stanu wiedzy: W pracy przytoczono rezultaty badań, do których włączono pacjentów z wirusem RSV, HIV, HAV, HBV, HCV. Potwierdzają one obecność markerów diagnostycznych poszczególnych zakażeń w ślinie, wskazując tym samym na możliwość wykorzystania śliny w diagnostyce chorób wirusowych. Podsumowanie: Wysoka czułość, dokładność, silna korelacja ze stopniem zaawansowania choroby, to bez wątpienia cechy, jakie wykazują badania wykonywane w surowicy krwi. Wymagają one jednak zaawansowanej aparatury, są kosztowne, dość inwazyjne, trudne w przechowywaniu. Ważne jest zatem, aby poszukiwać nowych metod, możliwych do wykorzystania w badaniach screeningowych. Badania takie powinny łączyć technologie szybkiego wykrywania z zastosowaniem łatwego do pobrania materiału. Coraz częściej podkreśla się potencjał śliny, jako materiału diagnostycznego do tego rodzaju badań. Słowa kluczowe: ślina, wirusy, diagnostyka, infekcje. Summary Introduction: Results in recent years have confirmed that most of substances contained in the blood serum also exist in the saliva. Significant correlations were found between salivary and serum levels. Saliva as a diagnostic test material in compare to other body fluids has many advantages and its importance is growing. During the last decades viral diseases morbidity and mortality rates improved. However late detection of viral infections is still the most Aim of the study: The aim of the study is to present the possibilities of using saliva in the screening of viral diseases. Short description of state of knowledge: The study presents results of studies which included patients with RSV, HIV, HAV, HBV, HCV. These confirms the presence of the diagnostic markers in saliva, indicating the possibility of using saliva in the diagnosis of viral diseases. Summation: Analysis made in the blood serum display characteristics such as high sensitivity, precision and a strong correlation with stadium of disease. However, they require the advanced apparatus, are expensive, very invasive, difficult to store. It is important to looking for a new methods that can be used in screening test which should connect rapid detection technology with using easy-to-sample collection. Increasingly, emphasizes potential of saliva as a diagnostic material for this kind of research. Key words: saliva, viruses, diagnostics, infection.